The Effect of Transformational Leadership of School Principles and Teacher Integrity on the Quality of High School Graduates in the Toraja Utara District - Arniati Batu Sumbung; Bernadetha Nadeak; Hotmaulina Sihotang (Budapest International Research and Critics University, 2022)
The study was conducted to analyze the influence of Principal Transformational Leadership and Teacher Integrity on the Quality of High School Graduates in North Toraja Regency, with quantitative methods, namely conducting descriptive analysis and testing hypotheses. the method used is quantitative. The regression equation between transformational leadership and graduate quality is Y ̂= -58,233+0,878 X1. While the results of the t-test calculation, there is a positive and significant influence of the principal's transformational leadership (X1) on the quality of high school graduates in North Toraja Regency (Y). The coefficient of determination of the two variables is 0.632 or 63.2%, meaning that the influence of the principal's transformational leadership on the quality of graduates is 63.2%. The regression equation between teacher integrity and the quality of graduates is Y ̂= -1,655+0,724 X2 and according to the results of the t-test, it is found that there is a positive and significant effect of teacher integrity (X2) on the quality of high school graduates in North Toraja Regency (Y). The value of the coefficient of determination of the two variables is 0.292 or 29.2%, meaning that the influence of the teacher integrity variable on the quality of graduates is 29.2%. The multiple linear regression equation between transformational leadership, teacher integrity, and the quality of graduates is Y ̂= -61,020+0,782 X1+0,219 X2and from the results of the F test calculation there is a positive and significant influence on the transformational leadership of principals and teacher integrity together on the quality of high school graduates in North Toraja Regency. The value of the coefficient of multiple determination (R2) is 0.651 or 65.1%, which means that the influence of principal transformational leadership and teacher integrity together on the quality of high school graduates in North Toraja Regency is 65.1%.